Self-Organized Clustering Architecture for Vehicular Ad Hoc Networks - Cándido Caballero-Gil; Pino Caballero-Gil; Jezabel Molina-Gil (International Journal of Distributed Sensor Networks)
Vehicular Ad Hoc NETworks (VANETs) are likely to be deployed in the near future. Then, they will become the platform for much of the relayed information in the Internet of Things. This paper proposes a new system based on 1-hop clustering to reduce the number of VANET communications in dense road traffic scenarios while maintaining the security of communications by combining public-key with secret-key cryptography. The proposed distributed clustering architecture creates a dynamic virtual backbone in the network, formed by Cluster-Heads and cluster-gateways, so that these nodes are responsible for the efficient message propagation in the network. The main aim of the described architecture is to balance both stability of backbone connections and cost/efficiency trade-off. Full definitions of all the architecture procedures are provided, including a cluster-head selection algorithm based on a version of the independent set problem and a secret-key agreement scheme that uses the generalized Diffie-Hellman protocol. Simulations show that the proposal improves network performance and security.